Predictive role of P-wave axis abnormalities in secondary cardiovascular prevention. (29th August 2020) - Lazzeroni, Davide; Bini, Matteo; Camaiora, Umberto; Castiglioni, Paolo; Moderato, Luca; Ugolotti, Pietro Tito; Brambilla, Lorenzo; Brambilla, Valerio; Coruzzi, Paolo
Abstract: Background: Abnormal P-wave axis has been correlated with an increased risk of all-cause and cardiovascular mortality in a general population. We aimed to evaluate the prognostic role of abnormal P-wave axis in patients undergoing myocardial revascularisation or cardiac valve surgery. Methods: We considered data of 810 patients with available P-wave axis measure from a prospective monocentric registry of patients undergoing cardiovascular rehabilitation. A total of 436 patients (54%) underwent myocardial revascularisation, 253 (31%) valve surgery, 71 (9%) combined valve and coronary artery bypass graft surgery and 50 (6%) cardiac surgery for other cardiovascular disease. Mean follow-up was 47 ± 27 months. Results: Over the whole group, P-wave axis was 43.8° ± 27.5° and an abnormal P-wave axis was found in 94 patients (12%). The risk of overall (hazard ratio (HR) 2.5, 95% confidence interval (CI) 1.6–4.0, P  < 0.001) and cardiovascular mortality (HR 2.9, 95% CI 1.5–5.8, P  = 0.002) was significantly higher in patients with abnormal P-wave axis even after adjustment for age, other electrocardiographic variables (PR, QRS, QTc intervals), left ventricular ejection fraction and left atrial volume index. After dividing the population according to the type of disease, patients with abnormal P-wave axis and ischaemic heart disease had 3.9-fold higher risk of cardiovascular mortality (HR 3.9, 95% CI 1.3–12.1, P  = 0.017), while a 2.2-fold higher risk of cardiovascular mortality (HR 3.6, 95% CI 1.3–10.1, P  = 0.015) was found in those with cardiac valve disease. Conclusion: An abnormal P-wave axis represents an independent predictor of both overall and cardiovascular mortality in patients undergoing myocardial revascularisation or cardiac valve surgery.